Eradication of Ventricular Assist Device Driveline Infection in Paediatric Patients with Taurolidine - Weichsel, Johannes; Baldauf, Benito; Bonnemeier, Hendrik; Lau, Ernest W.; Dittrich, Sven; Cesnjevar, Robert (Journal of Cardiovascular Development and Disease, 2022)
Ventricular assist devices (VADs) are used to provide mechanical circulatory support to patients with end-stage heart failure. The driveline connecting the external power source to the pump(s) of the intra-corporal VAD breaches the protective skin barrier and provides a track for microbes to invade the interior of the patient's body. Driveline infection constitutes a major and potentially fatal vulnerability of VAD therapy. Driveline infection cannot traditionally be salvaged and requires the extraction of the entire VAD system. We report here the successful eradication of a VAD driveline infection with a taurolidine-containing antimicrobial solution used for preventing the infection of cardiac implantable electronic devices. If replicated in more cases, the novel treatment concept described here may provide a valuable alternative management strategy of salvage rather than explantation for VAD driveline infection.
CRIS-Team WoS Importer:2022-02-04